2022
DOI: 10.3390/polym14061212
|View full text |Cite
|
Sign up to set email alerts
|

Void Content Determination of Carbon Fiber Reinforced Polymers: A Comparison between Destructive and Non-Destructive Methods

Abstract: The properties of composite materials are highly dependent on the fiber and matrix fraction and on the porosity resulting from micro voids. This paper addresses void content characterization and the constituent content of composite materials by resorting to a comparison of destructive and non-destructive methods. The work presents the detailed procedures of two destructive methods, using acid digestion of epoxy resins matrices, and compares their processes. It also presents the results of a non-destructive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The results of the void determination tests of the different samples showed that the void content is less than 2%, the percentage recommended by [15]. The void content according to the non-destructive testing was 1.531%, and the Fiber/Matrix ratio according to the destructive one was 57.6 / 41.1 [37]. Judging by the results, the manufacturing facilities were deemed safe for the next phase, and the quality of the product will be according to standards.…”
Section: Numerical Simulationmentioning
confidence: 84%
See 2 more Smart Citations
“…The results of the void determination tests of the different samples showed that the void content is less than 2%, the percentage recommended by [15]. The void content according to the non-destructive testing was 1.531%, and the Fiber/Matrix ratio according to the destructive one was 57.6 / 41.1 [37]. Judging by the results, the manufacturing facilities were deemed safe for the next phase, and the quality of the product will be according to standards.…”
Section: Numerical Simulationmentioning
confidence: 84%
“…Figure 8 shows some of the practical results of the two tests. A detailed description of the tests and the tests procedures has been described in previous work [37]. The results of the void determination tests of the different samples showed that the void content is less than 2%, the percentage recommended by [15].…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the void determination tests of the different samples indicated that the content being less than 2%, the percentage recommended by Mallick [17]. The void content according to the non-destructive testing was 1.531%, and the Fiber/Matrix ratio according to the destructive one was 57.6 / 41.1 [39]. Judging by the results, the manufacturing facilities were deemed safe for the next phase, and the quality of the product will be in line with standards.…”
Section: Quality Control 1) Constituent Content Of the Materialsmentioning
confidence: 86%
“…Figure 8 shows some of the practical results of the two tests. A detailed description of the tests and the tests procedures has been reported in previous work [39].…”
Section: Quality Control 1) Constituent Content Of the Materialsmentioning
confidence: 99%